2014
DOI: 10.1016/j.virusres.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Profile of natural killer cells after a previous natural Vaccinia virus infection in an in vitro viral re-exposure

Abstract: The present study compares the profile of NK cells in an in vitro re-exposure by Vaccinia virus (VACV), in groups that have had a previous vaccination or natural infection. Our data suggests that stimulation with VACV triggers a cytotoxic response by NK cells marked by an increase of NCRs: NKp30, NKp44, and NKp46 in infected (vaccinated and unvaccinated) subjects and in non-infected vaccinated patients, when compared with non-infected unvaccinated individuals. However, the degranulation and secretion processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…2H). A previous study with human NK cells from whole blood stimulated in vitro by UV-inactivated VACV showed that VACV-stimulated NK cells contained lower percentages of CD107a(+) cells than controls receiving media without inactivated VACV (Moreira-Silva et al, 2014). Although these data appear contradictory to our own observations with regard to the percentages of CD107a(+) NK cells, they still indicate that exposure to VACV causes a decrease in the percentage of NK cells bearing CD107a on their surface.…”
Section: Resultsmentioning
confidence: 92%
“…2H). A previous study with human NK cells from whole blood stimulated in vitro by UV-inactivated VACV showed that VACV-stimulated NK cells contained lower percentages of CD107a(+) cells than controls receiving media without inactivated VACV (Moreira-Silva et al, 2014). Although these data appear contradictory to our own observations with regard to the percentages of CD107a(+) NK cells, they still indicate that exposure to VACV causes a decrease in the percentage of NK cells bearing CD107a on their surface.…”
Section: Resultsmentioning
confidence: 92%
“…The observed increase in the CCL22 in OVA immunized NCR1 gfp/gfp mice did not reach significance in comparison to OVA immunized NCR1 +/+ mice. Thus, there might be additional mediators that control the migration of lymphocytes to the site of inflammation following OVA immunization [6568]. …”
Section: Discussionmentioning
confidence: 99%